2013
DOI: 10.1002/jso.23456
|View full text |Cite
|
Sign up to set email alerts
|

HER2 in resected gastric cancer: Is there prognostic value?

Abstract: HER2 amplification/over-expression is present in patients with resected gastric adenocarcinoma, but is not associated with the presence of adverse prognostic factors. Our results suggest HER2 is not prognostic for patients with resected gastric adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
0
22
1
Order By: Relevance
“…Although some studies have reported that HER2 positivity is a poor prognostic factor in gastric cancer [8][9][10][11], others have found that HER2 has no influence on prognosis [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have reported that HER2 positivity is a poor prognostic factor in gastric cancer [8][9][10][11], others have found that HER2 has no influence on prognosis [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to breast cancer in which HER2 is known as a poor prognostic factor [7], the prognostic value of HER2 in gastric cancer is still controversial. Even though some studies have shown that HER2-positivity in gastric cancer is associated with poor outcomes and less sensitive to cytotoxic chemotherapy [8][9][10][11], others have demonstrated that HER2 expression does not influence overall prognosis in gastric cancer [12][13][14][15]. Moreover, it has been getting harder to determine the prognostic value of HER2 per se in AGC after routine prescription of trastuzumab for HER2-positive patients, which can significantly prolong OS [6].…”
Section: Introductionmentioning
confidence: 99%
“…The HER2 overexpression is more frequently observed in gastroesophageal junction tumours than in those with distal gastric location and it is more often associated with the intestinal type adenocarcinomas [83–90]. Cancers positive for HER2 overexpression are usually differentiated tumours [43, 80, 91]. ERBB2 gene mutation that leads to HER2 overexpression occurs in the early stage of carcinogenesis [92].…”
Section: Her2mentioning
confidence: 99%
“…Although the role of HER-2 in this tumor has already been extensively investigated [19], and found to be frequently associated with invasion, high grade, and unfavorable prognosis, its overall prognostic role remains controversial [20-24] and appears to be stage-dependent.…”
Section: Her-2 As a Key Target In Gastric Cancers And Gastroesophageamentioning
confidence: 99%